Tatalaksana pengobatan karsinoma serviks uteri stadium inoperabel dengan radioterapi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1990)
Cancer of the cervix uteri is the most frequent cancer among Indonesian women. Treatment and prognosis depend on the stage of the disease determined during the first examination. Panhysterectomi and lymphadenectomi is the drug of choice for stages I and IIA. Stages D B and III A are considered inoperable and, therefore, external beam radiation therapy combined with intracavitair brachytherapy should be administered. The cure rate of stage I and II with surgical treatment is approximately 90%. The prognosis is less favourable for the inoperable stage and poor for stage IV.